2020
DOI: 10.1007/s12975-020-00850-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 27 Quantitative tractography revealed that there were more reconstructed CST fiber pathways in ICH patients with favorable outcomes. 28 Based on the results above, treatment with OMT significantly alleviated ICH‐induced CST axon injury and demyelination at cervical enlargement, which is perhaps due to the protection of OMT against WMI in the primary lesion, or its inhibition of astrocytes/microglia activation and inflammatory response. Prolonged activation of microglia induced by myelin debris has long been implicated in aggravating inflammatory action by secreting pro‐inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“… 27 Quantitative tractography revealed that there were more reconstructed CST fiber pathways in ICH patients with favorable outcomes. 28 Based on the results above, treatment with OMT significantly alleviated ICH‐induced CST axon injury and demyelination at cervical enlargement, which is perhaps due to the protection of OMT against WMI in the primary lesion, or its inhibition of astrocytes/microglia activation and inflammatory response. Prolonged activation of microglia induced by myelin debris has long been implicated in aggravating inflammatory action by secreting pro‐inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 81%
“…In stroke patients, the integrity of the CST was a determining factor for the proportional recovery of motor impairment [38]. Quantitative tractography revealed that there were more reconstructed CST ber pathways in ICH patients with favorable outcomes [39]. Our study revealed that treatment with OMT signi cantly alleviated ICH-induced CST axon injury and demyelination at cervical enlargement, which is perhaps due to the protection of OMT against WMI in the primary lesion, or it's inhibition of astrocytes/microglia activation and in ammatory response.. Additionally, detecting the immunophenotype of glial cells, we found that ICH activated more microglia and more astrocytes colabeled with GFAP and CSPG in the CST region of the cervical enlargement, suggesting that ICH caused CST destruction in the cervical enlargement, which subsequently induced microglia and astrocytes activation, while OMT signi cantly inhibited their activation and in ammatory response in the CST after ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To optimize the prognostic accuracy as well as the choice of appropriate treatment for patients with idiopathic normal pressure hydrocephalus, a valid imaging biomarker for beneficial shunt surgery would be highly desirable. A wide variety of predictive imaging biomarkers has been reported, such as the penumbra in stroke, 3 diffusion metrics in intracerebral haemorrhage 4 and traumatic brain injury 5 , or tumor grading with magnetic resonance spectroscopy (MRS) 6 and chemical exchange saturation transfer (CEST) imaging 7 . This shows that by the use of advanced imaging methods, information on disease status and outcome can be obtained more and more noninvasively.…”
mentioning
confidence: 99%